New algorithms to minimize handoff latency in AMTree protocol - Al-Sharafi, Ali; Othman, Mohamed; K. Subramaniam, Shamala (Zarqa University, 2009)
In active networks, programs can be injected to network elements (routers/switches). This allows programmers to enhance existing protocols or deploy new protocols. AMTree protocol is an active network based protocol that makes sending packets to receivers, after source migration, an efficient process. In AMTree protocol, after source migration, handoff latency computed from the time of reconnecting to a new base station until finding nearest core to the mobile source. In this paper the authors present two new algorithms to minimize the handoff latency in AMTree protocol. They show that handoff latency is much lower than that of AMTree handoff algorithm if the mobile source connects to a base station which is subscribed to the multicast group.